2018
DOI: 10.6065/apem.2018.23.3.126
|View full text |Cite
|
Sign up to set email alerts
|

Childhood diabetes in India

Abstract: This review describes the epidemiology of childhood diabetes in India. It focuses on the incidence and prevalence of type 1 diabetes and its complications and comorbid conditions. The review also covers data related to type 2 diabetes, glucose intolerance, and monogenic diabetes from India. A brief discussion regarding unique contributions from India to the world literature is included. The topics discussed include use of camel milk as adjuvant therapy in type 1 diabetes, relevance of the A1/A2 hypothesis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…In 2017, Chia et al ( 14 ) reviewed animal-based and in vitro evidence, concluding that A1 β-CN and BCM-7 were the dominant triggers of type 1 diabetes in individuals with genetic risk factors ( 14 ). This was in accordance to the observation of Kalra and Dhingra ( 15 ), who reported the hypothesis that exposure to A1/A1 β-CN milk of exotic breeds, such as those from India, might be linked with the rising incidence of type 1 diabetes. On the same topic, Kohil et al ( 25 ) concluded that specific dietary patterns can exert a direct impact on pathogenesis of type 1 diabetes through epigenetic modifications and that BCM-7 could act as an epigenetic modulator, differentially methylating genes involved in type 1 diabetes development.…”
Section: Methodssupporting
confidence: 92%
“…In 2017, Chia et al ( 14 ) reviewed animal-based and in vitro evidence, concluding that A1 β-CN and BCM-7 were the dominant triggers of type 1 diabetes in individuals with genetic risk factors ( 14 ). This was in accordance to the observation of Kalra and Dhingra ( 15 ), who reported the hypothesis that exposure to A1/A1 β-CN milk of exotic breeds, such as those from India, might be linked with the rising incidence of type 1 diabetes. On the same topic, Kohil et al ( 25 ) concluded that specific dietary patterns can exert a direct impact on pathogenesis of type 1 diabetes through epigenetic modifications and that BCM-7 could act as an epigenetic modulator, differentially methylating genes involved in type 1 diabetes development.…”
Section: Methodssupporting
confidence: 92%
“…Chia et al [ 89 ] reviewed animal-based trials and in vitro assays and concluded that A1 β-casein and BCM-7 were the dominant triggers of type 1 diabetes in individuals with genetic risk factors. This was consistent with those reported [ 95 ], who hypothesized that exposure to A1 β-casein milk is related to the rising incidence of type 1 diabetes, and Kohil et al [ 96 ], who postulated that BCM-7 could act as an epigenetic modulator, differentially methylating genes involved in type 1 diabetes development.…”
Section: Implications For Human Health Of Dairy β-Caseins and β-Casom...supporting
confidence: 92%
“…Although there are few population-based registries available in India to show the prevalence of childhood T1D, the increase of the disease could still be found in the population. Additionally, prevalences were the lower in rural areas and girls, suggested the lack of medical facilities and the poor healthcare-seeking behavior for the girls [14].…”
Section: Reviewmentioning
confidence: 99%